2021
DOI: 10.3390/vaccines9101099
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice of Main Stakeholders towards Human Papilloma Virus Infection and Vaccination in Mombasa and Tana-River Counties in Kenya: A Qualitative Study

Abstract: Following a successful Human Papilloma Virus (HPV) vaccination pilot in 2013–2015 in Kitui county, Kenya introduced the HPV vaccine in October 2019 with a goal to immunize approximately 800,000 girls annually against HPV. Our study assessed the knowledge, attitudes, and practice of affected groups towards HPV infection and vaccination in two counties of Kenya. Semi-structured interviews from children aged between nine and thirteen years and key informants comprising of parents, head teachers, community leaders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 55 publications
(75 reference statements)
3
8
0
Order By: Relevance
“…Of concern is that approximately 10% of parents were hesitant to have their children vaccinated, with safety concerns (76%) a notable reason. This is similar other studies in Kenya revealing safety concerns [ 11 , 17 , 29 , 30 ] alongside inadequate information [ 20 ]. Lack of knowledge regarding the HPV vaccine among health care workers, alongside misinformation that the vaccine is a form of contraception and encourages pre-marital sex, are concerns that need to be addressed going forward [ 29 , 30 , 64 , 65 ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Of concern is that approximately 10% of parents were hesitant to have their children vaccinated, with safety concerns (76%) a notable reason. This is similar other studies in Kenya revealing safety concerns [ 11 , 17 , 29 , 30 ] alongside inadequate information [ 20 ]. Lack of knowledge regarding the HPV vaccine among health care workers, alongside misinformation that the vaccine is a form of contraception and encourages pre-marital sex, are concerns that need to be addressed going forward [ 29 , 30 , 64 , 65 ].…”
Section: Discussionsupporting
confidence: 89%
“…This is similar other studies in Kenya revealing safety concerns [ 11 , 17 , 29 , 30 ] alongside inadequate information [ 20 ]. Lack of knowledge regarding the HPV vaccine among health care workers, alongside misinformation that the vaccine is a form of contraception and encourages pre-marital sex, are concerns that need to be addressed going forward [ 29 , 30 , 64 , 65 ]. Consequently, there needs to be efforts among all key stakeholders to alleviate safety and other concerns, with vaccination rates in Rwanda improved following multiple interventions [ 16 , 66 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…A qualitative study carried out among main stakeholders out in two counties in the North Eastern and coastal regions of Kenya sought to establish their knowledge, attitudes and practice regarding HPV infection and vaccination. Findings revealed that knowledge gaps among the interviewees were the largest contributor to vaccination refusal ( 18 ). It is therefore imperative that all stakeholders should be equipped with accurate information regarding HPV infection as a cause of cervical cancer as well as how vaccination provides protection.…”
Section: Hpv Vaccine Introduction In Routine Immunization and The Cha...mentioning
confidence: 99%
“…FBOs have played a vital role in healthcare development (14). As Palinkas, Pickwell (15) point out, health departments have utilised FBOs as a means of enabling messages to reach the masses who inhabit remote areas.…”
Section: Introductionmentioning
confidence: 99%